PEMBELAJARAN TEKS PROSEDUR KOMPLEKS MEMBACA PUISI SISWA KELAS X SMKN 1 BANDARLAMPUNG - Nikmatul Hasanah; Mulyanto Widodo; Eka Sofia Agustina (FKIP Universitas Lampung, 2014)
The purpose of this research is to describe the learning process of procedure text in reading poetry at the first year students of SMK Negeri 1 Bandarlampung. The research used descriptive qualitative method. The result of the research showed that the teacher had done three activities including planning, implementation, and assessment of learning. The teacher had made complete lesson plan according to the components of lesson plan in 2013 curriculum. In the implementation of learning, there were two activities: teacher’s activities and student’s activities. Teacher’s activities in the implementation of learning process included three activities: pre activity, while activity, and post activity. The assessment that was done by the teacher was skill competence assessment using practice test to know the ability of the students in implementing the principles in the procedure of reading poetry.Tujuan penelitian ini untuk mendeskripsikan pembelajaran teks prosedur membaca puisi pada siswa kelas X SMK N 1 Bandarlampung. Penelitian ini menggunakan metode deskriptif kualitatif. Hasil penelitian menunjukkan bahwa guru telah melakukankan tiga kegiatan yang mencakup perencanaan, pelaksanaan, dan penilaian pembelajaran. Perencanaan pembelajaran (RPP) yang dibuat oleh guru telah lengkap berdasarkan komponen – komponen RPP pada kurikulum 2013. Pada pelaksanaan pembelajaran terdapat dua aktivitas, yaitu aktivitas guru dan aktivitas siswa. Aktivitas guru pada pelaksanaan pembelajaran meliputi kegiatan pendahuluan, inti dan penutup. Penilaian yang dilakukan oleh guru adalah penilaian keterampilan menggunakan teknik tes praktik untuk mengetahui kemampuan siswa melaksanakan prinsip-prinsip pada prosedur membaca puisi.Kata kunci: membaca, pembelajaran, puisi, teks prosedur kompleks.